Partial characterization of the β-galactosidase gen from Bacillus sp. MSP7 isolated from Pilluana Saltern, San Martin - Peru - Zavaleta, Amparo I. (2013)
The β-galactosidases (EC3.2.1.23) are glycosyl hydrolases which mainly catalyze the hydrolysis of β-D-galactosides in various types of microorganisms, which are used in the synthesis of oligosaccharides. One of the potential sources for the production of enzymes that show these characteristics are microorganisms from extreme environments, such as salt brine. In this study, was cloned and characterized the betagalactosidase gene from Bacillus sp MSP7 isolated from Pilluana saltern in San Martin, Peru, because it shown enzymatic activity of 65 U/mg dried cells, the greatest activity than other four Bacillus sp. strains isolated from same village. For this, specific primers were designed from regions of consensus amino acid sequences of the Bacillus genus from available betagaltosidase sequences in data banks. Betagalactsidase gene of Bacillus sp. MSP7 was amplified by polymerase chain reaction generating an amplicon of approximately 2000 bp, this product was purified and joined to the pUC19 vector, Escherichia coli JM109 was used, the recombinant clones were sequenced partially. The nucleotide and amino acid sequences were analyzed using bioinformatics tools such as Blast, Clustal, Mega. The 957 bp nucleotide sequence of the beta-galactosidase gene showed 98% of similarity with its corresponding from Bacillus licheniformis ATCC 14580 (DSM 13), and to amino acid level had 99% similarity with the same strains. The protein belong to glycosyl hidrolase family 42.